Experimentation with Solid Steel Fibre Waste from Lathe as Backfill Material Affecting Earth Resistance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Safety is the major aspect of power systems. Earthing is a bypass mechanism which offers low resistance to protect personnel and equipment. The technology and industry growth in all over world witness benefits and lots of challenges posing serious environmental issues. Solid waste generated by lathe machines need to be disposed well or utilised. This paper details experimentations with steel waste fibresobtained of lathes used as a backfill material for earthing. Primary factors affecting earth resistance are earth electrode, soil resistivity and contact resistance between electrode and soil. The scrap lowered the earth resistance by 90% in wet condition when used with bentonite. Its effect is more profound in presence on bentonite.